Proposal to remove the visa requirement for Ecuadorian citizens: scenarios and strategies - Hidalgo Tandazo, Ramiro (2013)
This article analyzes the historical evolution of migration flows between Ecuador and Europe. There is a new European migration to Ecuador and other South American countries, in spite of which the European Union has not adjusted its immigration policy to this new reality. Therefore, there is a need for the EU to remove the visa requirement for Ecuadorean citizens. The article presents some scenarios and strategies to achieve that goal, including a proposal of solidarity and collective action of UNASUR on visas.